Fulvic acid-iron colloid promotes the migration of As(III) in porous media - Yanhao Li; Youru Yao; Xinyi Wang; Huimin Zhang; Fengman Fang; Yuesheng Lin; Zhiming Zhang; Qing Ji; Jia Yu (Journal of Contaminant Hydrology, 2026)

Steering active hydrogen in PtCu single atom alloy nanowires for efficient nitrate reduction to ammonia - Weimian Zhang; Binwen Zeng; Haoliang Huang; Fan Dang; Xin Liu; Jing Sun; Wei Liao; Mengxiang Han; Chao Song; Run Ran; Kaiyang Xu; Fei Lin; et al. (Chemical Engineering Journal, 2026)

Mechanism of heterogeneous mixing between typical oxygenated volatile organic compound and hematite: implication for radiative forcing - Yongpeng Ji; Linghao Kong; Jiaxin Wang; Baocong Zhao; Zhiming Zhang; Shengping Chen; Sihao Lin; Jiangyao Chen; Yanpeng Gao; Yuemeng Ji (Atmospheric Environment, 2026)

Deep seismic sounding methods for imaging the fine structure of the Earth’s crust - Yurui Guan; Tao Xu; Zhiming Bai; Jiyan Lin; Dengda Zhu; Jiwen Teng (Science China Earth Sciences, 2026)

Effects of Temperature on Artificial Breeding and Early Development of Osteochilus salsburyi - Yang Yang; Yutian Gong; Guoliang Li; Qi Su; Shifeng Guan; Haitao Zheng; Lin Xu; Feng Chen; Xuan Zhao; Zhiming Zhang (Fishes, 2026)
To determine the optimal water temperature range for artificial breeding and early development of Osteochilus salsburyi, six water temperature gradients (14, 18, 22, 26, 30, and 34 °C) were set to systematically investigate the effects of water temperature on artificial reproduction efficiency, embryonic development, the morphology of newly hatched larvae, larval growth performance, and the timing of organ development in O. salsburyi. The results showed that the spawning induction rate of O. salsburyi reached 100% at 14–30 °C. The fertilization rate and hatching rate peaked at 18–22 °C, and no fertilization was completed at 34 °C. The malformation rates of embryos and larvae showed a U-shaped change, with the lowest malformation rate at 18 °C, and the teratogenic effect of high-temperature stress was more significant. The embryonic development rate was significantly negatively correlated with water temperature, and the development duration was significantly shortened with increasing water temperature. Embryonic development was arrested and all embryos died at 34 °C, while hatching could be completed at 14 °C but with an excessively long cycle. The morphological indicators of newly hatched larvae showed differentiated sensitivity to water temperature; total length, pre-anal length, and body height were highly sensitive indicators, and larvae exhibited balanced and robust morphological development at 18–22 °C. The larval survival rate first increased and then decreased with increasing water temperature, reaching the highest rate at 22–26 °C. The absolute growth increment, relative growth increment, and specific growth rate (SGR) continued to increase with increasing water temperature. The timing of larval organ differentiation and behavioral development was significantly advanced with increasing water temperature. Late organ development of larvae was blocked at 14 °C, only early development was completed at 34°C, and the internal and external organs of larvae developed completely and in an orderly manner at 18–30 °C. In summary, the optimal water temperature for artificial breeding and early development of O. salsburyi is 18–26 °C, among which 18–22 °C is the best for artificial reproduction and 22–26 °C is optimal for larval rearing. The results can provide a scientific basis for the precise regulation of water temperature in large-scale seedling production of O. salsburyi.

Optimization of multi-enzyme coupled debittering process: Effect on bitterness and bioactive components of Shatianyu (Citrus grandis L. Osbeck) whole fruit powder - Lin Zhang; Ruifen Zhang; Mingwei Zhang; Zhenlin Xu; Fei Huang; Xuchao Jia; Lihong Dong; Zhiming Wang; Mei Deng (Food Chemistry, 2026)

Molting disruption in fall armyworm by an ankyrin-based Bracovirus factor from the parasitoid wasp Microplitis prodeniae Rao and Chandry - Yaru Wang; Farman Ullah; Liuying Lin; Xiangyun Cai; Ge Gao; Limin Chen; Zhiming Chen; Raul Narciso C. Guedes; Yaobin Lu; Jinda Wang; Youming Hou (Journal of Pest Science, 2026)

Molecular-weight-dependent mixing behavior of organic phosphorus and carbon in a subtropic river-estuary-bay continuum - Cheng Xu; Ying Huang; Bin Yang; Renming Jia; Zhiming Ning; Bo Yang; Lei Xie; Lin Yang; Dongliang Lu; Zhenjun Kang; Laodong Guo (Water Research, 2026)

The Study on the Application of Time-Lapse Double-Difference Tomography Theory in the 3D Velocity Structure Distribution of Tunnel Surrounding Rock - Hongyun Yang; Zhiming Zhang; Xiang Wang; Yifei Wu; Zhi Lin; Yong Li; Xiang Chen; Wanlin Feng; Chuandong Jiang (Rock Mechanics and Rock Engineering, 2026)

Smoldering Combustion-Based calorimeter integrated with Dual-GRU network for online coal Quality analysis - Xuegang Zhang; Haiyuan Fu; Zhiming Lin; Qiwen Jin; Pengcheng Jiang; Xuecheng Wu (Fuel, 2026)

Spatiotemporal variability, partitioning and mixing behavior of dissolved and particulate phosphorus in a typical subtropical river-estuary-bay continuum - Lin Yang; Bin Yang; Fan Yang; Mufeng Zhong; Dongdong Zhu; Zhiming Ning; Zhenjun Kang; Dongliang Lu; Jiaodi Zhou; Guodong Song (Marine Pollution Bulletin, 2026)

Mechanistic impacts of extra-long tunnel construction on eco-environmentally vulnerable zones: Coupled system dynamics and LSTM-Transformer modelling - Yan Yin; Weixing Bao; Hanqing Lu; Zhiming Huang; Xuhui Lin (Tunnelling and Underground Space Technology, 2026)

CAU-Net: An attention-based feature enhancement model for ground-based cloud image segmentation applicable to peri-solar regions - Junye Zhu; Yutong Liu; Kefan Xu; Yangshu Lin; Keqi Wang; Zhiming Lin; Qiwen Jin; Chao Yang; Lijie Wang; Chenghang Zheng; Yongxin Zhang; Xuecheng Wu (Advances in Space Research, 2026)

Application of nanomaterials in central nervous system disorders - Yixuan Deng; Yani Feng; Bangming Ye; Lei Hu; Lixin Qi; Chenyi Wang; Chunting Zhou; Guanhao Liu; Xiuying Gao; Congying Lin; Qiang Ding; Ziming Zhao; et al. (Psychopharmacology, 2025)

AlgaeDiff-Net: A novel computational framework for automated microalgae species identification and morphological analysis - Shihuan Luo; Yiheng Niu; Jiayi Tang; Danyan Yang; Xintao Lin; Biwen Yang; Zerong Guan; Yifan Zhou; Huiqing Zhong; Zhiming Liu; Zhouyi Guo (Algal Research, 2025)

Comparative study of machine learning and deep learning in predicting the shear strength of marine sand and polymer layer interfaces interface under marine temperature effects - Zhiming Chao; Yanqi Liu; Dongbo Jiang; Hongbo Du; Wei You; Xianhui Feng; Jie Lin; Peng Cui; Zejin Wang (Frontiers in Marine Science, 2025)
In marine engineering, polymer layers are anti-seepage barrier materials. The mechanical interaction between marine sand and polymer layer significantly affects overall structural stability. In this study, direct shear tests at different temperatures in the marine environment are simulated to evaluate the shear behavior of marine sand and polymer layer interface, and a database is developed. Based on the experimental data, the study employs the Back propagation Neural Network (BPNN), Genetic Algorithm and Particle Swarm Optimization BPNN, and convolutional neural network (CNN) models, which are trained and tested. The findings show that the CNN algorithm significantly outperforms other models in terms of prediction accuracy and efficiency. Sensitivity analysis shows that temperature, shear displacement, normal stress, and particle size have influence on interfacial shear strength, and the impact of normal stress is the greatest. In addition, an empirical formulation is proposed to provide tools for those without machine learning. Based on the research results, the deep learning CNN model developed in the study can accurately predict the shear strength of the interface between marine sand and the polymer layer, which provides an effective tool for the design and optimization of marine engineering.

Hydrocarbon organic conjugated skeleton with multi-sites functionalization for non-doped ultraviolet organic light-emitting diodes with CIEy = 0.029 - Jing Yang; Jingli Lou; Mingjian Ni; Zhiqiang Zhuo; Hao Li; Xiang An; Ning Sun; Mengyuan Li; Xuehua Ding; Lizhi Wang; Man Xu; Xueqin Ran; et al. (Chemical Engineering Journal, 2025)

Atomic dispersion of scandium in electrochemically reduced copper oxide nanosheets for efficient electrocatalytic CO2 reduction to C2+ products - Yang Zhao; Binwen Zeng; Haoliang Huang; Huanhuan Yang; Zhipeng Yu; Chao Song; Jingwei Wang; Kaiyang Xu; Xinyi Xiang; Wei Wang; Fei Lin; Sheng Meng; et al. (Chemical Engineering Journal, 2025)

Comparison between different major data assimilation algorithms on region tobacco growth simulation - Zhenxin Lin; Jihua Meng; Xinyan You; Zhiming Hua; Rongpeng He; Baofeng Jiao; Hongchao Zhao; Quanxiang Yan (Computers and Electronics in Agriculture, 2025)

Genome-wide identification of ApeC domain-containing protein and revealing the function of ChACP-1.10 in oyster mucosal immunity - Tianxiang Lin; Lu Liu; Liang Zeng; Congxin Zhao; Shu Xiao; Haitao Ma; Jun Li; Fan Mao; Yanping Qin; Yuehuan Zhang; Yang Zhang; Zhiming Xiang; et al. (Fish & Shellfish Immunology, 2025)

Immunomodulatory effect of Qihuang Biwen decoction and its postbiotic product - Junxiang Li; Mingqian Wang; KangKang Liu; Yibo Liang; Haijuan Wang; Yang Lin; Zeqi Huo; Zhiming Zhang; Chunjiang Zhang (World Journal of Microbiology and Biotechnology, 2025)

Macrophage-targeted lipid nanoparticles based on Dendron-like lipids deliver mTOR inhibitor to alleviate systemic lupus erythematosus - Keqian Du; Guantao He; Fujian Huang; Xi Zhang; Xiaohan Zhang; Junjin Jie; Chan Huang; Yuqiong Wu; Huiyang Fan; Zhiming Lin; Lin-Ping Wu (Chemical Engineering Journal, 2025)

Diffusion of sodium ions based on the interactions between gum arabic and oral mucin: Effects from the molecular weight of gum arabic - Yanlei Li; Ruiting Chang; Lin Lu; Zhiming Gao; Yuehan Wu; Wenxin Jiang; Dan Yuan; Katsuyoshi Nishinari (Food Chemistry, 2025)

Plasmonic nanoheater for formaldehyde degassing - Gaopan Chen; Peng Yu; Lian Yang; Roberto Caputo; Feng Lin; Liang Pan; Yang Gao; Hongxing Xu; Alexander Govorov; Zhiming Wang (Chemical Engineering Journal, 2025)

Functional molecule surface infiltration treatment for efficient all-inorganic perovskite light-emitting diodes - Shurui Chi; Yongjian Chen; Xiuling Li; Jiaqi Wang; Zixun Zhao; Zhuojian Li; Yanqin Miao; Xin Tong; Jinli Liu; Yuechuan Bi; Zongwen Liu; Zhiming Wang; et al. (Chemical Engineering Journal, 2025)

Chrysoeriol: a natural RANKL inhibitor targeting osteoclastogenesis and ROS regulation for osteoporosis therapy - Hao Luo; Sijian Lin; Hao Lv; Wen Tan; Junlong Zhong; Jiachao Xiong; ZhiMing Liu; Qin Wu; Ming Chen; Kai Cao (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Corrigendum to “Recirculating aquaculture system as microbial community and water quality management strategy: a rearing mode for improved viability of crab larvae” [Water Research Volume 252, Mar 2024] - Zhibin Lu; Weichuan Lin; Qiang Li; Qingyang Wu; Zhiming Ren; Changkao Mu; Chunlin Wang; Ce Shi; Yangfang Ye (Water Research, 2025)

Effect of hydraulic residence time on nitrogen removal from a synthetic mariculture wastewater using a bench-scale recirculating bioreactor embedded with aerobic denitrifying bacteria Marinobacter alkaliphilus strain JY28 - Shilin Lin; Jinming Ma; Yi Du; Wenxin Wang; Jing Wang; Mengchun Gao; Chunji Jin; Yangguo Zhao; Zhiming Zhang; Junyuan Ji (Journal of Environmental Management, 2025)

Dynamic response of vegetation to meteorological drought and driving mechanisms in Mongolian Plateau - Shenghang Gao; Shengzhi Huang; Vijay P. Singh; Xiaoya Deng; Limin Duan; Guoyong Leng; Wenwen Guo; Yifei Li; Lin Zhang; Zhiming Han; Qiang Huang (Journal of Hydrology, 2025)

Deep percolation and soil water dynamics under different sand-fixing vegetation types in two different precipitation regions in semiarid sandy Land, Northern China - Liang He; Yiben Cheng; Wenbin Yang; Jianbin Guo; Zhiming Xin; Lin Chen; Wei Xiong; Qianqian Wang; Huaiyuan Liu (Agricultural and Forest Meteorology, 2025)

Why Super Typhoon Occurrence Over the Western North Pacific Ocean Tends to be More in Autumn Than Summer - Zhiming Feng; Xiuping Yao; Chenfei Liao; Jiali Ma; Ning Pan; Yanluan Lin (International Journal of Climatology, 2025)
Based on the tropical cyclone (TC) best‐track datasets from the China Meteorological Administration during 1949–2020 and the fifth generation ECMWF atmospheric reanalysis (ERA5) datasets, we investigate the characteristics of super typhoons (SuperTYs) over the western North Pacific (WNP) and associated mechanism in this study. The results show that SuperTYs are prone to occur in autumn over the WNP, nearly 30% of the autumn TCs develop into SuperTYs, and autumn SuperTYs account for more than half of the annual total. This is due to both favourable oceanic and atmospheric conditions. In southeastern WNP, the sea surface temperature (SST) in autumn is higher than that in summer, inducing zonal circulation anomalies and enhancing low‐level westerlies. Consequently, the monsoon trough strengthens and extends eastward, favouring enhanced autumn typhoon occurrence in the southeastern WNP. This southeastward shift facilitates TCs to remain over the warm ocean for a longer period and makes them more prone to develop into SuperTYs. Furthermore, TCs tend to take westward‐moving tracks in autumn due to stronger easterly steering flows compared with summer, resulting in more TCs passing over the South China Sea (SCS) to the east of the Philippines where the vertical wind shear (VWS) is relatively weaker and prone to develop into superTYs.

CircRNA ITCH Inhibits Epithelial–Mesenchymal Transformation and Promotes Apoptosis in Papillary Thyroid Carcinoma via miR-106a-5p/JAZF1 Axis - Yijun Chen; Zhiming Lian; Guolie Zhang; Yuanmei Lin; Guoliang Zhang; Wei Liu; Jian Gao; Zifang Zheng (Biochemical Genetics, 2024)
Circular RNA ITCH (circ-ITCH) is implicated in papillary thyroid carcinoma (PTC) development. Nevertheless, the more detailed molecular mechanism remains uncovered. The transcriptional level of circ-ITCH was tested via quantitative real-time PCR. Transwell assay was introduced to assess the migrative and invasive abilities of cells. RNA interference technology was employed to reduce the level of circ-ITCH as well as JAZF1 in PTC cells. Western blot assay was utilized to reveal the content of JAZF1 and proteins related to epithelial–mesenchymal transformation (EMT) progression. Circ-ITCH was downregulated in PTC tissues as well as cells. Overexpression of circ-ITCH suppressed EMT, migration, invasion, facilitated apoptosis in PTC cells, while silencing circ-ITCH exhibited reversed effects. Additionally, miR-106a-5p was the target of circ-ITCH and negatively regulated through circ-ITCH. MiR-106a-5p mimic partly eliminated the influences of overexpressed circ-ITCH in PTC cells. Moreover, JAZF1 could interact with miR-106a-5p, then it was regulated via circ-ITCH. Silencing JAZF1 partially counteracted the role of circ-ITCH in PTC cells progress. This study uncovered that circ-ITCH suppressed the development of PTC cells at least partly by mediating miR-106a-5p/JAZF1 network.

The Temperature-Dependent Monotonic Mechanical Characteristics of Marine Sand–Geomembrane Interfaces - Zhiming Chao; Hongyi Zhao; Hui Liu; Peng Cui; Danda Shi; Hai Lin; Yang Lu; Bing Han; Shuang Chen (Journal of Marine Science and Engineering, 2024)
The utilization of geomembrane reinforcement technology is pervasive in marine sand foundation reinforcement projects. However, the elevated temperatures and intricate stress conditions prevalent in marine environments exert a notable influence on the mechanical characteristics of geomembrane interfaces comprising marine sand, which impedes the efficacy of geomembrane reinforcement in marine sand foundations. Nevertheless, there is a lack of research investigating the temperature-dependent interfacial mechanical performance of geomembranes and marine sand under diverse stress states. In this study, a series of monotonic shear tests were carried out on the interface between geomembranes and marine sand within a temperature range of 5 °C to 80 °C. These experiments were carried out using a self-developed large-scale temperature-controlled interfacial dynamic and static shear device. The experimental results demonstrate that temperature has a pronounced effect on the monotonic mechanical characteristics of the geomembrane–marine sand interface, which displays clear temperature dependence. The findings of this study may help in the design and optimization of offshore projects where a marine sand–polymer layer interface exists.

Comparative study of dynamic characteristics between a FHAWT and a helical type FVAWT - Wanru Deng; Liqin Liu; Zihe Lin; Zhiming Yuan; Yan Li; Dongsheng Liu; Haoran Li; Ying Guo (Ocean Engineering, 2024)

ChCaspase-1 cleaves ChGasdermin-E, inducing pyroptosis, and participates in the bacterial defence of the oyster Crassostrea hongkongensis - Liang Zeng; Tianxiang Lin; Lu Liu; Congxin Zhao; Ruwen Yang; Shu Xiao; Fan Mao; Yanping Qin; Haitao Ma; Yuehuan Zhang; Yang Zhang; ZiniuYu; et al. (Aquaculture, 2024)

Low-temperature NH3 abatement via selective oxidation over a supported copper catalyst with high Cu+ abundance - Zhiming Yang; Lin Peng; Leneng Yang; Mingli Fu; Daiqi Ye; Peirong Chen (Journal of Environmental Sciences, 2024)

Development of an online dual-cylinder open calorimeter for coal powder: An experimental investigation - Xuecheng Wu; Xuegang Zhang; Zhiming Lin; Qiwen Jin; Sirui Jiang; Linghong Chen; Yingchun Wu; Kefa Cen (Fuel, 2024)

ChRIPK1 caused necroptosis signaling pathway deficiency in Crassostrea hongkongensis - Yucheng Yang; Liang Zeng; Tianxiang Lin; Lu Liu; Congxin Zhao; Shu Xiao; Haitao Ma; Jun Li; Fan Mao; Yanping Qin; Yuehuan Zhang; Yang Zhang; et al. (Fish & Shellfish Immunology, 2024)

A shallow (<100 km) ilmenite-bearing pyroxenitic source for young lunar volcanism - Chengyuan Wang; Yi-Gang Xu; Le Zhang; Zhiming Chen; Xiaoping Xia; Mang Lin; Feng Guo (Earth and Planetary Science Letters, 2024)

Spatiotemporal Characteristics of Typical Ecosystem Services and Their Spatial Responses to Driving Factors in Ecologically Fragile Areas in Upper Yellow River, China - Gui Liang; Fengman Fang; Yuesheng Lin; Zhiming Zhang (Chinese Geographical Science, 2024)

Synergistic selenium doping and colloidal quantum dots decoration over ZnIn2S4 enabling high-efficiency photoelectrochemical hydrogen peroxide production - Hongyang Zhao; Yisen Yao; Mengke Cai; Xin Li; Peihang Li; Ali Imran Channa; Feng Lin; Mingzhu Wang; Zhiming M. Wang; Xin Tong (Chemical Engineering Journal, 2024)

3D shape and size characterization of micron-sized coal particle with XRCT and SH - Qiwen Jin; Zhiming Lin; Yingchun Wu; Xuecheng Wu (Fuel, 2024)

Dual-attention LSTM autoencoder for fault detection in industrial complex dynamic processes - Lei Zeng; Qiwen Jin; Zhiming Lin; Chenghang Zheng; Yingchun Wu; Xuecheng Wu; Xiang Gao (Process Safety and Environmental Protection, 2024)

Strengthening the diffusion of sodium ions by interactions between gum Arabic and oral mucin - Yanlei Li; Ruiting Chang; Duanyang Zhu; Lin Lu; Zhiming Gao; Yuehan Wu; Wenxin Jiang; Dan Yuan (Food Hydrocolloids, 2024)

Trifluoperazine activates AMPK / mTOR / ULK1 signaling pathway to induce mitophagy in osteosarcoma cells - Wenhui Shen; Xiangchen Zeng; Xianhui Zeng; Baoshan Hu; Chong Ren; Zhiming Lin; Long Zhang; Gang Rui; Miersalijiang Yasen; Xiaohui Chen (Chemico-Biological Interactions, 2024)

Polymeric microenvironment enhancing polarity response sensitivity for discriminating lipid droplets in cancer cells - Yujing Zuo; Zhiming Gou; Weiying Lin (Analytica Chimica Acta, 2024)

Recirculating aquaculture system as microbial community and water quality management strategy in the larviculture of Scylla paramamosain - Zhibin Lu; Weichuan Lin; Qiang Li; Qingyang Wu; Zhiming Ren; Changkao Mu; Chunlin Wang; Ce Shi; Yangfang Ye (Water Research, 2024)

Novel cytochrome P450s for various hydroxylation of steroids from filamentous fungi - Guojuan Yi; Hanlu Zou; Tao Long; Tolbert Osire; Lin Wang; Xiaoyun Wei; Mengfei Long; Zhiming Rao; Guojian Liao (Bioresource Technology, 2024)

Dissolved organic matter and Fe/Mn enhance the combination and transformation of As in Lake Chaohu Basin - Youru Yao; Kang Ma; Shiyin Li; Yong Zhang; Zhiming Zhang; Fengman Fang; Yuesheng Lin; Li Yin; Lian Sun; Chonghong Zhang (Journal of Environmental Management, 2024)

Preclinical evaluation of RQ3013, a broad-spectrum mRNA vaccine against SARS-CoV-2 variants - Shudan Tan; Jinghua Zhao; Xue Hu; Yufeng Li; Zihan Wu; Guoliang Lu; Zhaoli Yu; Binhe Du; Yan Liu; Li Li; Yuchen Chen; Ye Li; et al. (Science Bulletin, 2023)

Research on on-site measurement factors and performance of coal calorific value based on laser ignition - Xuegang Zhang; Linglong Wang; Qiwen Jin; Zhiming Lin; Chenghang Zheng; Yingchun Wu; Xuecheng Wu (Fuel, 2023)

Selective hydrocracking of poly-aromatics to mono-aromatics in a catalyst grading system of NiMo/Al2O3-HY and NiMo/Beta - Lin Qi; Chong Peng; Zhenmin Cheng; Zhiming Zhou (Fuel, 2023)

Three-dimensional flow and turbulence structure around Sea Cucumber Apostichopus japonicus - Yubing Lin; Haifei Liu; Zhiming Ru; Gangqin Tu; Zixin Wang (Ocean Engineering, 2023)

Creb2 involved in innate immunity by activating PpMitf-mediated melanogenesis in Pteria penguin - Feifei Yu; Zexin Du; Zhiming Zhong; Xiangyong Yu; Jiayu Chen; Yishan Lu; Jinji Lin (Fish & Shellfish Immunology, 2023)

Development of a toughened and antibacterial Poly(lactide acid) (PLA) with preserved strength by elemental sulfur-based bio-renewable dynamically crosslinked elastomers - Xiaojie Chen; Ruanquan Zhang; Yixuan Mao; Liling Zhong; Peiyao Lin; Qizhe Deng; Botuo Zheng; Hang Shen; Zhiming Feng; Huagui Zhang (Chemical Engineering Journal, 2023)

Analysis of the evolutionary game between maritime regulators and carriers under the discharge of ballast nuclear wastewater from ships - Jun Jiang; Zhiming Ma; Li Lin; Yiping Yuan; Xiaona Fu (Ocean & Coastal Management, 2023)

TLR4 involved in immune response against Vibrio Parahaemolyticus by MyD88-dependent pathway in Crassostrea hongkongensis - Feifei Yu; Jiayu Chen; Jinji Lin; Zhiming Zhong; Yishan Lu; Xiangrong Zeng; Xiaoya Lei (Fish & Shellfish Immunology, 2023)

The earliest Neoproterozoic Nb-enriched mafic magmatism indicates subduction tectonics in the southwestern Yangtze Block, South China - Fenglin Chen; Xiaozhuang Cui; Shoufa Lin; Jian Wang; Guangming Ren; Kuizhou Li; Mingda Huang; Zhiming Sun; Shilei Liu; Peng Wang; Weihua Pang (Precambrian Research, 2023)

Synergistic trimetallic Ni–Cu–Sn catalysts for efficient selective hydrogenation of phenylacetylene - Wei Chen; Huawu Xu; Xiaoling Ma; Lin Qi; Zhiming Zhou (Chemical Engineering Journal, 2023)

Natural variation of the BRD2 allele affects plant height and grain size in rice - Jinpeng Huang; Zhiming Chen; Jiajia Lin; Jinwen Chen; Menghao Wei; Liang Liu; Feng Yu; Zesen Zhang; Fangyu Chen; Liangrong Jiang; Jingsheng Zheng; Tiansheng Wang; et al. (Planta, 2022)

Legacy effects of a multi-year extreme drought on belowground bud banks in rhizomatous vs bunchgrass-dominated grasslands - Jianqiang Qian; Ziyue Guo; Taofeek O. Muraina; Niwu Te; Robert J. Griffin-Nolan; Lin Song; Chong Xu; Qiang Yu; Zhiming Zhang; Wentao Luo (Oecologia, 2022)

The origin and source of natural gas in the Lower Permian in Hewanchang area, Northwest Sichuan - Kaijun Tan; Yaoting Li; Jianbo Liao; Zhiming Xu; Zhanghao Liu; Zonghui Lin (Arabian Journal of Geosciences, 2022)

Climate Suitability Assessment of Human Settlements for Regions along the Belt and Road - Yumei Lin; Peng Li; Zhiming Feng; Yanzhao Yang; Zhen You; Fuxin Zhu (Chinese Geographical Science, 2021)

Dynamic Detection of Thrombolysis in Embolic Stroke Rats by Synchrotron Radiation Angiography - Liping Wang; Panting Zhou; Zhihao Mu; Xiaojie Lin; Lu Jiang; Zhuo Cheng; Longlong Luo; Zhiming Xu; Jieli Geng; Yongting Wang; Zhijun Zhang; Guo-Yuan Yang (Translational Stroke Research, 2019)

Long non-coding RNA RP11-6O2.4 indicates poor prognosis and suppresses cell cycle progression through the p38-MAPK signaling pathway in gastric cancer - Yang Feng; Zhiming Fu; Yajun Luo; Wang Tan; Zilin Liu; Pengcheng Ye; Fei Lu; Wanping Xiang; Linghan Tang; Lin Yao; Mengyun Song; Qingmei Huang; et al. (Molecular & Cellular Toxicology, 2019)

Genome-wide association analysis of lead accumulation in maize - Xiongwei Zhao; Yajuan Liu; Wenmei Wu; Yuhua Li; Longxin Luo; Yuzhou Lan; Yanhua Cao; Zhiming Zhang; Shibin Gao; Guangsheng Yuan; Li Liu; Yaou Shen; et al. (Molecular Genetics and Genomics, 2018)

Identification of antibiotic mycelia residue in protein rich feed using on near-infrared microscopy imaging - Yufei Lin; Zengling Yang; Hao Liang; Shouxue Li; Xia Fan; Zhiming Xiao (Food Additives & Contaminants: Part A, 2018)

Winter wheat straw return monitoring by UAVs observations at different resolutions - Kun Yu; Lin Qiu; Jingjing Wang; Ling Sun; Zhiming Wang (International Journal of Remote Sensing, 2017)

Effect of sustained training on glycolysis and fatty acids oxidation in swimming muscles and liver in juvenile tinfoil barb Barbonymus schwanenfeldii (Bleeker, 1854) - Zhiming Zhu; Bolan Song; Xiaotao Lin; Zhongneng Xu (Fish Physiology and Biochemistry, 2016)

Molecular characterization of melanin-concentrating hormone (MCH) in Schizothorax prenanti: cloning, tissue distribution and role in food intake regulation - Tao Wang; Dengyue Yuan; Chaowei Zhou; Fangjun Lin; Rongbin Wei; Hu Chen; Hongwei Wu; Zhiming Xin; Ju Liu; Yundi Gao; Defang Chen; Shiyong Yang; et al. (Fish Physiology and Biochemistry, 2016)

Identification and characterization of differentially expressed microRNAs in response to Rhizoctonia solani in maize - Mao Luo; Haijian Lin; Jian Gao; Wanrong Li; Yaou Shen; Maojun Zhao; Guangtang Pan; Zhiming Zhang (Acta Physiologiae Plantarum, 2015)

A putative pathogen-resistant regulatory pathway between MicroRNAs and candidate target genes in maize - Jian Gao; Mao Luo; Chun Zhang; Hua Peng; Haijian Lin; Yaou shen; Maojun Zhao; Guangtang Pan; Zhiming Zhang (Journal of Plant Biology, 2015)

QTL analysis of three flower-related traits based on an interspecific genetic map of Luffa - Junjie Cui; Jiaowen Cheng; Guoping Wang; Xin Tang; Zhiming Wu; Mingbao Lin; Lianfang Li; Kailin Hu (Euphytica, 2015)

Schizothorax prenanti corticotropin-releasing hormone (CRH): molecular cloning, tissue expression, and the function of feeding regulation - Tao Wang; Chaowei Zhou; Dengyue Yuan; Fangjun Lin; Hu Chen; Hongwei Wu; Rongbin Wei; Zhiming Xin; Ju Liu; Yundi Gao; Zhiqiong Li (Fish Physiology and Biochemistry, 2014)

Genome-wide analysis of Water-stress-responsive microRNA expression profile in tobacco roots - Fuqiang Yin; Jian Gao; Ming Liu; Cheng Qin; Wenyou Zhang; Aiguo Yang; Mingzhong Xia; Zhiming Zhang; Yaou Shen; Haijian Lin; Chenggang Luo; Guangtang Pan (Functional & Integrative Genomics, 2014)

Genome expression profile analysis of the maize sheath in response to inoculation to R. solani - Jian Gao; Zhe Chen; Mao Luo; Hua Peng; Haijian Lin; Cheng Qin; Guangsheng Yuan; Yaou Shen; Haiping Ding; Maojun Zhao; Guangtang Pan; Zhiming Zhang (Molecular Biology Reports, 2014)

Different Gene Expressions of Resistant and Susceptible Maize Inbreds in Response to Fusarium verticillioides Infection - Guangsheng Yuan; Zhiming Zhang; Kui Xiang; Yaou Shen; Juan Du; Haijian Lin; Li Liu; Maojun Zhao; Guangtang Pan (Plant Molecular Biology Reporter, 2013)

Aberrant methylation and loss expression of RKIP is associated with tumor progression and poor prognosis in gastric cardia adenocarcinoma - Wei Guo; Zhiming Dong; Yanli Guo; Xinwen Lin; Zhifeng Chen; Gang Kuang; Zhibin Yang (Clinical & Experimental Metastasis, 2013)

Renin–Angiotensin System Modulates Neurotransmitters in the Paraventricular Nucleus and Contributes to Angiotensin II-Induced Hypertensive Response - Jie Qi; Dong-Mei Zhang; Yu-Ping Suo; Xin-Ai Song; Xiao-Jing Yu; Carrie Elks; Yuan-Xi Lin; Yan-Yan Xu; Wei-Jin Zang; Zhiming Zhu; Yu-Ming Kang (Cardiovascular Toxicology, 2013)

Cloning and characterization of miRNAs from maize seedling roots under low phosphorus stress - Zhiming Zhang; Haijian Lin; Yaou Shen; Jian Gao; Kui Xiang; Li Liu; Haiping Ding; Guangsheng Yuan; Hai Lan; Shufeng Zhou; Maojun Zhao; Shibin Gao; et al. (Molecular Biology Reports, 2012)

Cytoplasmic male sterility-regulated novel microRNAs from maize - Yaou Shen; Zhiming Zhang; Haijian Lin; Hailan Liu; Jie Chen; Hua Peng; Moju Cao; Tingzhao Rong; Guangtang Pan (Functional & Integrative Genomics, 2011)

Multiple generations of pseudotachylyte in the brittle to ductile regimes, Qinling–Dabie Shan ultrahigh‐pressure metamorphic complex, central China - Aiming Lin; Zhiming Sun; Zhenyu Yang (Island Arc, 2003)
Pseudotachylytes are present along the Dahezhen shear zone in the Qinling–Dabie Shan collisional orogenic belt, central China. Two types of pseudotachylyte vein are documented in the shear zone: cataclasite‐related pseudotachylyte (C‐Pt) and mylonite‐related pseudotachylyte (M‐Pt). M‐Pt is associated with mylonite‐development and is overprinted by C‐Pt. All of the quartz and most of the feldspar porphyroclasts within the M‐Pt are plastically deformed, but not in the C‐Pt. Dynamically recrystallized fine‐grained quartz and feldspar bands are oriented subparallel to the mylonite and M‐Pt foliation, and partially surround the porphyroclasts. Our results suggest that the M‐Pt formed cyclically in the ductile region at estimated conditions of 400–650°C and 400–800 MPa due to propagation of seismic fracturing associated with the thrusting‐related rapid exhumation of the ultrahigh‐pressure metamorphic complex in the brittle regime down to a greater depth than the base of the seismogenic zone. The M‐Pt and mylonite formed in the Dahezhen shear zone at estimated conditions of 400–650°C and 400–800 MPa. The coexistence of C‐Pt and M‐Pt in the same shear zone suggests that repeated seismic slips occurred in both the brittle and ductile portions of the crust during the thrusting‐related rapid exhumation of the ultrahigh‐pressure metamorphic complex.